Eccentric distance zone analysis system: New regional evaluation of cephalic fixator tip location for predicting cut-out in geriatric intertrochanteric fractures with internal fixation - Yang, Yun-fa; Huang, Jian-wen; Gao, Xiao-sheng; Xu, Zhong-he (Frontiers in Surgery, 2022)
Objective: To investigate an eccentric distance (ED) zone analysis system for regional evaluation of the cephalic fixator tip based on the ED of the cephalic fixator tip referenced to the radius of its own femoral head to predict cut-out in intertrochanteric fractures (ITF) with internal fixation. Methods: Firstly, we assumed all the femoral head was a regular sphere with the radius of the femoral head (RFD) of “3” for a complete match of the Cleveland zone system and calculated the ED of the cephalic fixator tip by measuring the distances from the cephalic fixator tip to the geometric central axis in the femoral neck and head on both AP view and lateral view radiographs. Secondly, we defined the maximum transverse section of the femoral head into three zones named ED Zone A with ED less than “1”, Zone B with ED ranging in “1-2”, and Zone C with ED ranging in “2-3” in turns by concentric circles (circle A, B, and C) with the radius of 1/3, 2/3, and 3/3 times of RFD, respectively. Thirdly, we evaluated the ED zones according to the ED and location of the cephalic fixator tip in the eligible 123 ITF patients with single-screw cephalomedullary nail (SCMN) fixation and then analyzed the correlation between the cut-out rate and the ED zones. Results: The cut-out rate in ED Zone A, B, and C was 4.17%, 38.46%, and 100%, respectively. Multivariate logistic regression indicated that ED Zone A had at least a 14 times lower rate of cut-out compared with ED Zone B. The cephalic fixator tip located in ED Zone A has a lower cut-out rate than that in Cleveland Zone 5. The cut-out rate in ED Zone A is significantly lower than that in the region inside Cleveland Zone 5 but outside ED Zone A. Conclusion: ED zone analysis system is a reliable regional evaluation of the cephalic fixator tip position for predicting cut-out in geriatric ITF patients with SCMN fixations and potentially an artificial intelligence measurement during surgery. For decreasing the cut-out rate, the cephalic fixator tip should be located in ED Zone A.